Protective effect of liquiritin on coronary heart disease through regulating the proliferation of human vascular smooth muscle cells via upregulation of sirtuin1. Issue 2 (1st February 2022) - Yuan, Liang; Wang, Dajie; Wu, Chunyang
ABSTRACT: This study aimed to explore whether liquiritin affects the development of coronary heart disease by regulating the proliferation and migration of human vascular smooth muscle cells (hVSMCs). A 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyl-2 H-tetrazolium bromide (MTT) assay and lactate dehydrogenase (LDH) release detection were performed to measure the toxic effects of liquiritin on hVSMCs. An in vitro atherosclerosis model in hVSMCs was established using oxidized low-density lipoprotein (ox-LDL), and cell proliferation and apoptosis were detected using an MTT assay and flow cytometry analysis. Western blotting and reverse transcriptase quantitative polymerase chain reaction (RT-qPCR) were used to detect protein and mRNA expressions, respectively. Caspase3 activity and cell migration were measured using an activity detection kit and Transwell assay, respectively. The results indicated that liquiritin at doses <160 μM had no significant effect on cell viability and LDH release in hVSMCs. Ox-LDL significantly induced cell proliferation and migration, and inhibited hVSMCs apoptosis. Liquiritin significantly inhibited cell proliferation and migration, and enhanced cell apoptosis in ox-LDL induced hVSMCs. Sirtuin1 (SIRT1) was lowly expressed in atherosclerotic plaque tissues in coronary heart disease patients and in ox-LDL-induced hVSMCs. Liquiritin improved SIRT1 expression in ox-LDL-induced hVSMCs, whereas the improvement was inhibited by Selisistat (EX 527, an effective SIRT1 inhibitor) treatment. EX 527 reversed the effects of liquiritin on cell proliferation, migration, and apoptosis in ox-LDL-induced hVSMCs In conclusion, liquiritin plays a protective role in coronary heart disease by regulating the proliferation and migration of hVSMCs by increasing SIRT1 expression.